Aortic graft infection with enteric organism after embolization of late type II endoleak - Ben Li, BHSc; Kong Teng Tan, MD; Mary Elizabeth MacDonald, MD, PhD; John Byrne, MB BCh, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2019)
An 82-year-old man with a history of endovascular repair for ruptured abdominal aortic aneurysm 6 years ago presented with a type II endoleak and enlarging sac. He had successful transabdominal direct sac puncture embolization but developed fever 2 days postoperatively. Contrast-enhanced computed tomography showed a rim-enhancing collection, and sac aspiration was positive for enteric organisms, confirming endograft infection. The patient underwent graft explantation and neoaortic reconstruction using superficial femoral veins. Three months postoperatively, computed tomography showed complete resolution of fluid collection and no signs of graft infection. This report illustrates direct puncture embolization complicated by endograft infection from enteric bacteria. Keywords: Abdominal aortic aneurysm, Endovascular aneurysm repair, Graft infection, Endoleak embolization, Aortic reconstruction